Pembentukan Karakter Peduli Lingkungan Siswa pada Sekolah Adiwiyata (Studi Kasus di Madrasah Ibtidaiyah Miftahul Ulum Kota Batu) - Zulfhadli, Mhd. (Journal of Islamic Education, 2024)
The adiwiyata program is a program that contains policies regarding environmentally sound schools as outlined in the Minister of Environment regulation no. 5 of 2013 concerning guidelines for the implementation of Adiwiyata. The Adiwiyata program aims to shape human character with environmental insight by creating an adequate environmental condition, both in science and in facilities and infrastructure related to good environmental management. Environmental care character is an attitude of caring for the environment by improving the quality of the environment, increasing school community awareness about the importance of caring for the environment and having initiatives to prevent environmental damage. The adiwiyata program is suspected of contributing to the formation of students' environmental care character. The purpose of this study was to analyze the formation of environmental care character of Madrasah Adiwiyata students at Madrasah Ibtidaiyah Miftahul Ulum in Batu City.This research is a type of descriptive qualitative research. The population of this research is all students of Madrasah Miftahul Ulum Batu City, while the research sample is 100 students in class VI. The data in the research is descriptive, which is presented in the form of words. Research data retrieval is done by observation, interviews and documentation.The results show that the environmental care character of Madrasah Ibtidaiyah Miftahul Ulum students has been formed with indicators (a) Maintaining the cleanliness of the classroom and school environment, (b) Supporting the go green program in the school environment, such as taking care of plants and using sufficient electricity, (c) ) Sorting organic and non-organic waste along with differentiating its shelters, and (d) Maintaining the cleanliness of the bathroom, water and hand washing areas.Keywords: Adiwiyata, Care for the Environment